2014
DOI: 10.4274/turkderm.57767
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis ve metabolik sendrom

Abstract: Background and Design:Psoriasis is a chronic, inflammatory disease that occurs with polygenic and other triggering factors. The association of psoriasis, which is considered to be a systemic disease, with other diseases, such as cardiovascular diseases, hepatosteatosis, obesity, diabetes mellitus, hypertension, and hyperlipidemia has been shown. Materials and Methods:In this study, we compared the levels of fasting blood glucose, serum lipid (total cholesterol, HDL cholesterol, triglyceride), basal insulin, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…23 According to the data from the Turkish Metabolic Syndrome Research, conducted in 2004 through screening of 4264 individuals, MBS prevalence was 41.1% in females, 28.8% in males, with an overall of 35%. 24 Günaydın et al 2 had found MBS in 31 (62%) of 50 psoriasis patients when they evaluated MBS components with laboratory investigations including fasting blood glucose, among others. Lower ratios found in our study may have resulted from the assessment of MBS components like diabetes, dyslipidemia and hypertension only in diagnosed patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 According to the data from the Turkish Metabolic Syndrome Research, conducted in 2004 through screening of 4264 individuals, MBS prevalence was 41.1% in females, 28.8% in males, with an overall of 35%. 24 Günaydın et al 2 had found MBS in 31 (62%) of 50 psoriasis patients when they evaluated MBS components with laboratory investigations including fasting blood glucose, among others. Lower ratios found in our study may have resulted from the assessment of MBS components like diabetes, dyslipidemia and hypertension only in diagnosed patients.…”
Section: Discussionmentioning
confidence: 99%
“… 27 The findings which suggest that cutaneous inflammation and neighboring fat tissue cytokines could induce hyper-proliferation of each other are as follows; i. 2 - 4 Definition of the receptors which mediate early immune response to antigens on the cell surface of adipocytes and release cytokines like interleukin-6 and tumor necrosis factor (TNF)-alpha, which are closely related to psoriasis development, ii. Higher production of circulating TNF-α, soluble TNF-α, and in vitro TNF-α in the obese compared to the non-obese, iii.…”
Section: Discussionmentioning
confidence: 99%
“…Günaydın var ark. (29) psoriasisli hastaların %62'sinde metabolik sendrom belirlemişlerdir. Tsai ve ark.…”
Section: Discussionunclassified
“…Psoriasis vulgaris is a chronic inflammatory disease that is observed in 1%-3% of the general population and is characterized by attack and remission periods (1,2). A combination of insulin resistance and metabolic syndrome (MetS) is commonly observed in psoriasis patients (3)(4)(5)(6). These patients also often suffer from hypertension (HT), heart failure, and diabetes mellitus (DM) (7).…”
Section: Introductionmentioning
confidence: 99%